Colour degradation of facade coatings - the effect of nanopigments incorporation - Nuno M. M. Ramos (2020)
The increasing interest in the use of a wide range of colours in buildings, especially dark colours, may lead to the early degradation of the facades, compromising their aesthetic and thermal performance. On the other hand, the incorporation of nanopigments with high reflectance properties can contribute to reducing the absorption of solar radiation. The nanoparticles contribute to increasing the solar reflectance of coatings, decreasing the surface temperature and improving the coating performance. This work evaluates the natural degradation of the colour of finishing coat with nanopigments in ETICS. The colour parameters were evaluated in different ETICS specimens, considering the colour black and red with and without incorporated nanopigments, under natural ageing. The colour measurement was performed according to ISO 1164-4, using a portable spectrophotometer. The results confirmed that the use of nanopigments improved the colour durability, promoting the maintenance of the colours parameters. The total colour difference was lower than the perceptible by the human eyes, even as the lower variation on chroma and hue parameters of the colours with nanopigments. In summary, the incorporation of nanoparticles in finishing coat of ETICS can contribute to increasing their durability and improve their thermal performance without compromising the aesthetic characteristics.